Reaction mechanism of azoreductases suggests convergent evolution with quinone oxidoreductases - Ryan, Ali (Protein Cell, 2010)
Azoreductases are involved in the bioremediation by bacteria of azo dyes found in waste water. In the gut flora, they activate azo pro-drugs, which are used for treatment of inflammatory bowel disease, releasing the active component 5-aminosalycilic acid. The bacterium P. aeruginosa has three azoreductase genes, paAzoR1, paAzoR2 and paAzoR3, which as recombinant enzymes have been shown to have different substrate specificities. The mechanism of azoreduction relies upon tautomerisation of the substrate to the hydrazone form. We report here the characterization of the P. aeruginosa azoreductase enzymes, including determining their thermostability, cofactor preference and kinetic constants against a range of their favoured substrates. The expression levels of these enzymes during growth of P. aeruginosa are altered by the presence of azo substrates. It is shown that enzymes that were originally described as azoreductases, are likely to act as NADH quinone oxidoreductases. The low sequence identities observed among NAD(P)H quinone oxidoreductase and azoreductase enzymes suggests convergent evolution. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13238-010-0090-2 and is accessible for authorized users.